GENDER DIFFERENCE STUDY ON BLACK FRIDAY & CYBER MONDAY SALES AMONG GENERATION Z IN CHENNAI CITY - Kamatchi Preethi Vasudevan, Dr. D.S. Selvakumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Online shopping has gained importance over this pandemic period. The preference to shop online has grown over the period of time. The objective of the study is to analyze gender difference on the Black Friday and Cyber Monday Sale in Chennai City among the age group of population between 17 to 22, to examine the gender difference on these Sale days in the online shopping whether they are need based or compulsive buying and to find the reasons for purchasing online through Friedman test. There are numerous online shopping platforms offering these kinds of sales on these particular days. The data was collected from 100 sample population who are undergraduate students from Chennai City. The sampling method used is random sampling technique. The sample size was 100, around 120 questionnaires were filled out. The fully completed questionnaire were utilized for the analysis. The Simple Percentage Analysis, Friedman Test and t -Test analysis are the tools used for the data analysis. The study shows that male respondents are more likely to be having a positive attitude towards the Black Friday and Cyber Monday Sales. The Sale days started on November 27 and ended on the November 30, 2020.